Molecular profiling and analysis of genetic aberrations aimed at identifying potential therapeutic targets in fibrolamellar carcinoma of the liver. Issue 18 (14th July 2020) - El Dika, Imane; Bowman, Anita S.; Berger, Michael F.; Capanu, Marinela; Chou, Joanne F.; Benayed, Ryma; Zehir, Ahmet; Shia, Jinru; O'Reilly, Eileen M.; Klimstra, David S.; Solit, David B.; Abou‐Alfa, Ghassan K.
Abstract : Background: Fibrolamellar carcinoma (FLC) is a rare primary liver cancer of young adults. A functional chimeric transcript resulting from the in‐frame fusion of the DNAJ homolog, subfamily B, member 1 ( DNAJB1 ), and the catalytic subunit of protein kinase A ( PRKACA ) genes on chromosome 19 is believed to be unique in FLC, with a possible role in pathogenesis, yet with no established therapeutic value. The objective of the current study was to understand the molecular landscape of FLC and to identify potential novel therapeutic targets. Methods: Archival fresh, formalin‐fixed, paraffin‐embedded samples from patients with FLC who prospectively consented to an institutional review board–approved protocol were analyzed using Memorial Sloan Kettering–Integrated Mutation Profiling of Actionable Cancer Targets (MSK‐IMPACT), a next‐generation sequencing assay encompassing up to 468 key cancer genes. Custom targeted RNA‐Seq was performed in selected patients. Demographics, treatment, and outcome data were collected prospectively. Survival outcomes were estimated and correlated with mutation and/or copy number alterations. Results: A total of 33 tumor samples from 31 patients with FLC were analyzed. The median age of the patients at the time of diagnosis was 18 years and approximately 53% were women. The DNAJB1‐PRKACA fusion transcript was detected in 100% of patients. In 10 of 31 patients in which MSK‐IMPACT did not detect the fusion, its presence was confirmed by targeted RNA‐Seq. TERT promoter mutation was the second most common, and was detected in 7 patients. The median follow up was 30 months (range, 6‐153 months). The 3‐year overall survival rate was 84% (95% CI, 61%‐93%). Conclusions: The DNAJB1‐PRKACA fusion transcript is nonspecific and nonsensitive to FLC. Its potential therapeutic value currently is under evaluation. Opportunities currently are under development for therapy that may be driven or related to the DNAJB1‐PRKACA fusion transcript or any therapeutic target identified from next‐generation sequencing in patients with FLC. Abstract : The potential therapeutic value of the DNAJ homolog, subfamily B, member 1 ( DNAJB1 ) and the catalytic subunit of protein kinase A ( PRKACA ) fusion transcript or any therapeutic target has yet to be identified. Opportunities currently are under development for therapy in patients with fibrolamellar carcinoma that may be driven or related to the DNAJB1‐PRKACA fusion transcript.